High‐pressure homogenization induced degradation of amylopectin in a gelatinized state. (10th March 2016) - Wei, Benxi; Cai, Canxin; Jin, Zhengyu; Tian, Yaoqi
Abstract : An investigation of the degradation mechanism of a highly branched polymer during a high‐pressure homogenization (HPH) process was performed using gelatinized waxy maize starch as a substrate. The degradation mechanism was studied using high‐performance size‐exclusion chromatography equipped with multi‐angle laser‐light scattering and refractive index detectors. The HPH induced an exponential molecular degradation trend that was a function of HPH pressure/cycles. The results revealed that HPH preferentially disrupted larger molecules and caused their size distribution (or molecular weight) to a narrow range, resulting in a maximum stable size (or molecular weight). A final z ‐average radius of gyration of about 20 nm for amylopectin was observed after HPH for eight cycles at 100 MPa or two cycles at 150 MPa, which was due to the midpoint scission mechanism during the HPH treatment. The increase in molecular density after HPH verified the breakdown of the α‐1, 4‐glycosidic bonds among the clusters of (midpoint scission) amylopectin.